A Systematic Review of Science Discourse in K–12 Urban Classrooms in the United States: Accounting for Individual, Collective, and Contextual Factors. (December 2021) - Bae, Christine L.; Mills, Daphne C.; Zhang, Fa; Sealy, Martinique; Cabrera, Lauren; Sea, Marquita
The literature on science discourse in K–12 classrooms in the United States has proliferated over the past couple of decades, crossing geographical, disciplinary, theoretical, and methodological boundaries. There is general consensus that science talk is at the core of students' learning; however, a synthesis of key findings from the expansive literature base is needed. This systematic literature review is guided by a complex systems framework to organize and synthesize empirical studies of science talk in urban classrooms across individual (student or teacher), collective (interpersonal), and contextual (sociocultural, historical) planes. Findings are discussed in relation to contemporary approaches that integrate theories and methodologies to account for the complex phenomena of science discourse, including interacting elements across levels as well as stable and changing patterns that influence students' access to, and nature of, science talk in urban classrooms. Unresolved questions related to high-leverage, equitable, and sustainable discourse practices; future lines of inquiry that can benefit by drawing from diverse theoretical traditions and mixed methodological approaches; and practical implications for classroom-based strategies to support science discourse are also discussed.